Decadal variability of rainfall in Senegal: beyond the total seasonal amount - Badji, Aissatou; Mohino Harris, Elsa; Diakhaté, Moussa; Mignot, Juliette; Gaye, Amadou Thierno (Journal of Climate, 2022)
Rainfall characteristics are crucial in monsoon regions, in particular for agriculture. Crop yields indeed depend on the rainfall seasonal amounts, but also on other rainfall characteristics such as the onset of the rainy season or the distribution of rainy days. In the Sahel region, while the average amount of seasonal rainfall has been shown to be marked by strong decadal variability, the modulation of rainfall characteristics has received less attention in the literature so far. In this study, we show that the frequency of light, heavy, and extreme rainfall events and the mean intensity of rainfall events in Senegal exhibit a marked decadal variability over the 1918–2000 period, strongly similar to that of the mean seasonal rainfall. The decadal modulations of these events show a strong and positive link with the Atlantic multidecadal variability (AMV). Indeed, positive sea surface temperature anomalies over the North Atlantic and Mediterranean related to a warm AMV phase are associated with negative sea level pressure anomalies over the northern Atlantic and a northward shift of the intertropical convergence zone. We also find that the onset and cessation dates as well as the length of the rainy season show relatively less decadal variability, which is more related to the interdecadal Pacific oscillation (IPO), a positive phase of the latter leading to a late onset, an early cessation, and an overall shorter rainy season in Senegal. Service de Cooperation et d'Action Culturelle of the French Embassy in Senegal Unión Europea Laboratoire Mixte International ECLAIRS2 (IRD) Universidad Complutense de Madrid European Commission TRIATLAS Ministerio de Ciencia e Innovación (España) Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub